LUSTMORD AND THE LIMITS OF REPRESENTATION (Palíndromo, 2018)
This paper analyses the work Lust-mord (1993), by the American visual artist Jenny Holzer, created in response to the atrocious events of sexual violence committed by Serbian soldiers agaist Muslim Women in war-torn Bosnia, from 1992 to 1995. Its objective is to think how Holzers’ work managed to assert itself in a culture already saturated with images of violence.
Keywords: Jenny Holzer; representations of violence; Lustmord; rape; visual culture